Pesan Kampanye Non-Goverment Organization terhadap Permasalahan Sampah Plastik - Wayan Weda Asmara Dewi; Wifka Rahma Syauki (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2022)
Abstract Environmental pollution from plastic waste has many negative impacts that can harm the earth's ecosystem now and in the future. Many non-governmental organizations (NGOs) have initiated changes in the use of plastics, in this research, Bye Bye Plastic Bags (BBPB). One of the efforts that can be done is to hold a campaign that aims to initiate a social change, especially in the use of plastic waste. Changes made with campaigns are always related to aspects of knowledge, attitudes, and behavior. This study aims to find out how the response from the community to the BBPB campaign message is related to the problem of plastic waste. The method used in this study uses descriptive quantitative research methods and seven main indicators. Based on the results of descriptive analysis of each of the seven campaign message indicators, good results were obtained. The dominant indicator in this research is the content indicator. It can be concluded that the campaign message carried out by Bye Bye Plastic Bags (BBPB) was well received by the public